PENGARUH MODEL PEMBELAJARAN MAKE A MATCH TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN BAHASA INGGRIS DI KELAS IV SD NEGERI 066050 MEDAN - Situmorang, Anita S; Gaol, Rumiris Lumban; Juliana, Juliana; Sinaga, Reflina; Simarmata, Ester Julianda (Universitas Negeri Medan, 2023)
This study seeks to determine the impact of the make a match learning model on student learning outcomes in English class IV SD Negeri 066050 Medan Learning Year 2022/2023. The research method used is experimental quantitative research methodology. To obtain information in the form of data, a test instrument of 30 questions is needed. The number of research samples was 30 students based on purposive sample technique. To see the initial ability of students, the study conducted a Pre Test with the results representing a set of scores of 59.87 which fell into the category of less. The results of the Post Test are better than the results of the Pre Test given previously with the average value of the students reaching 80.17 in the excellent category. The results of the calculation of the correlation coefficient show an increase in the level of student learning success where 14rhitung